Seeking Comfort - Bailey, Alison (East Carolina University, 2015)
I believe that objects once possessed by a loved one can vividly revive one's memories  and have the power to evoke comfort and nostalgia. The contrast, color, repetition, and tactile  qualities of my pieces preserve these memories. I work in metal because of its preciousness and  its permanence. I frame various fabrics with metal because of their contrasting properties.  Fabric is soft, retains scent, and is impermanent. The fabrics come from various sources; from  my grandmother, some are found, and others designed and printed by me. Seeking Comfort is a  body of work consisting of three series (Altered Spoons, Brooches, and Neckpieces). It is an  exploration of how the act of creating with these materials and concepts functions as a coping  mechanism.
Keywords: Fine arts; Design; Embroidery; Enamel; Metals; Ornaments; Textiles; Tradition; Metal-work; Art objects; Textile jewelry; Jewelry